how would you find the x and y intercepts of y=x^2+x-2?
Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga.
Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus.
Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
Well the easiest way would to be by graphing the function, but if we cant do that we can always algebraically figure it out
how would you solve graphically? I know the first step is to make either x or y equal 0
Not the answer you are looking for? Search for more explanations.
Well you are correct that is how we do it
To solve for the 'y intercept' we make x = 0
\(\large y = 0^2 + 0 - 2 \) meaning that \(\large y = ?\)
And now the x-intercept would be making y = 0
\[\large 0 = x^2 + x - 2\]
We can factor this or just brute force through it
to find the y-intercept we let x = 0
to find the x-intercept we let y = 0
so when x = 0, y = -2 so that would mean that our y-intercept is at (0,-2)
we can factor \[\large 0 = x^2 + x - 2 \]. and then solve for x. We would have more than one solution for our x-intercepts
thank you both!
so we need to focus on the last term 2 and the second term 1
there's only one combination
2 x 1 = 2 (so we got the last term)
we need to use subtraction to obtain one
so we have
\[\large 0 = (x+2)(x-1)\]
now we just split this up and solve for x in each case
\[\large 0 = x-1\],\[\large 0 = x+2 \]
so xint= -2 and 1 ?
yes our x = -2 and x = 1
so our x-intercepts are
(-2,0) and (1,0)
because we need y = 0 to obtain the x-intercepts.
first put y=0
so your equation will be0=x^2+x−2
then you will make it (x-1)(x+2)=0
so it will lead that x is equal to
1 and -2